SerViU: A Tool-Supported Method for Personalizing Telehealth Services - Aswad, Oday (Université d'Ottawa / University of Ottawa, 2022)
The personalization of telehealth services to accommodate patient preferences and interaction abilities could significantly improve patient adherence to telehealth treatment plans. Long-term adherence can be as low as 25% among chronic patients for reasons related to ease-of-use and personal preferences, which can be attributed to factors associated with the patient, physicians, and healthcare systems. Poor adherence in the long term can cause increased morbidity, poorer quality of life, a higher risk of mortality, and greater health care utilization. Poor adherence is partly driven by generic telehealth services that are not adapted to individual patients' lived experiences. Recent research calls for the personalization of telehealth services in a manner that addresses long-term adherence. This thesis views the telehealth service context from a multilevel service systems perspective. This perspective enables the articulation of the contextual differences between standardized and personalized services. This thesis proposes a service design method (SerViU: pronounced Serv You) to support a continuous Use - Assess - Personalize process; this design method focuses on the patient personal service encounter level within a telehealth service. SerViU is anchored in the service-dominant logic concept of value-in-use, and it assesses the patient's individualized experiences with the telehealth service and accordingly recommends a suitable personalization. SerViU guides decision-making about telehealth personalization by integrating an existing information communication technology (ICT) service personalization framework that identifies three types of ICT personalization: architectural, relational, and technological. A design science research methodology (DSRM) was used to guide the research activities underlying the development and validation of SerViU. Within this methodology, the SerViU Personalize Tool was selected to demonstrate SerViU's ability to personalize telehealth services by accounting for patient-related, service context-related, and technology-related factors. A multiple case study with embedded units of analysis was conducted at a Canadian hospital to simulate personalization decision-making using the SerViU Personalize Tool. The same participants were then asked to fill out a questionnaire to evaluate the tool's usefulness for decision-making, its relevance to the telehealth context, and whether it contained sufficient information to make personalization decisions. Results show that SerViU was relevant to telehealth contexts, useful for making personalization decisions, and provided sufficient information to make relevant decisions. The collected data were analyzed using cross- and within-case analysis by comparing decisions in different telemonitoring service modes. The comparisons included personalization options, feature selection, scores, rationales, and resource-related information. The results of this research provide a means to operationalize telehealth personalization as proposed in telehealth research. This study provides a method which can guide the transformation of generic telehealth services into personalized services. This research contributes to service design by differentiating between standard and personal service encounter levels, which is paramount for supporting the personalization of ICT-enabled services. This research contributes to the telehealth practice by presenting an ongoing telehealth personalization process that involves patients in decision-making throughout their treatment processes as a means to improving long-term adherence.
Keywords: Telehealth; Personalization; SerViU; Service-Dominant Logic